Implementasi Pendekatan Etnopedagogi Berbasis Kearifan Lokal Terhadap Pembelajaran Tematik Pada Guru Kelas - Fatmi, Nuraini; Faradhillah, Faradhillah; Sri Rezeki, Nimas; Mukrimah, Umi (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
The purpose of the study was to find out how the implementation of an ethnopedagogical approach based on local wisdom towards thematic learning in classroom teachers. The research method is field research (Field Research). The subjects of this study were teachers at SDN 1 Gampong Mesjid, Nurussalam District. Data collection techniques are observation techniques, interview/ interview techniques and documentation techniques. The findings of the research show that education based on local wisdom provides a positive response from teachers and students, this is because students can know and understand the content of Acehnese local wisdom contained in learning in schools. Covering theme 6 (Energy and its Changes) Class III through making banana sales, theme 4 (Always saving energy) Class IV through making Acehnese traditional houses, theme 6 (Heat and its displacement) Class V through making Acehnese adee cakes, theme 8 (My Earth) Class VI through Keuneunong custom, a calendar or calendar, theme 9 (Exploring Outer Space) Class VI through Keuneunong to determine the stars.